Analiza zależności wartości ekstremalnych a pomiar ryzyka - Heilpern, Stanisław (Analysis of tail dependence and measure of risk, 2008)
This paper is devoted to the tail dependence, i.e. the dependence for the small or big values of the random variables. These dependences are studied from the finance and insurance point of view, the management of risk mainly. The tail dependence coefficients and the tail dependence copulas are presented. The basic properties of these notions and the methods of estimation of such coefficients are studied. Two theorems, which let us analyze the tail dependences, are presented. One theorem is used to the approximation of the basic measures of risks: VaR and TailVaR.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 103-114